Effect of 10-year cumulative blood pressure exposure on atherosclerotic cardiovascular disease of different age groups: kailuan cohort study - Guo, Lu; Tian, Faming; Wang, Jingyao; Xu, Wenqi; Li, Wenjuan; Hou, Xiaoli; Zheng, Mengyi; Yang, Xuemei; Gao, Lishu; Chen, Shuohua; Zhang, Nan; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2024)
Background The level at which cumulative blood pressure (BP) can increase the risk of ASCVD in different age groups remains unclear. This study aimed to investigate the association of 10-year cumulative BP levels with the long-term risk of ASCVD of different age groups. Methods Cumulative BP exposure was assessed using the time-weighted average (TWA) BP divided into four BP groups. The participants were also divided into four groups according to their baseline age (<50, 50–59, 60–69, or ≥70 years). The association between TWA BP and the risk of ASCVD was assessed by age group using multivariate Cox models. The China-PAR prediction model was used to assess the ability of TWA BP to predict ASCVD. Results In the group aged <50 years, the hazard ratios and 95% confidence intervals for the risk of ASCVD were 2.66 (1.04–6.80), 3.38 (1.54–7.43), and 3.13 (1.36–7.24) for the elevated BP, stage 1 hypertension, and stage 2 hypertension groups, respectively, when compared with the normal BP group. There was a significant difference in the risk of ASCVD between the age groups, with participants aged <50 years having the highest risk, followed by those aged 50–59, 60–69, and ≥70 years. Conclusions The risk of ASCVD with high cumulative BP exposure was age-dependent, with a gradual decrease in risk with increasing age.